Pengaruh Kepercayaan Diri Terhadap Keterampilan Sosial Pada Mahasiswa - Meyfina Dwi Rahmawati; Wustari. L. Mangundjaya (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Interpersonal skills had influenced many things including the success in university. Meanwhile every individual need interpersonal skill when doing their activities. Social skills are defined as individual communication skills to undergo communication in socializing in college. In this research, the method used is quantitative with regression test. The aims of the research are to study the effect of self confidence on interpersonal skill. This study used a convenience sampling technique with 334 students as the respondents. The result of this study showed that self confidence can be a predictor of social skills, with contribution of 10,9 % and the rest is influenced by other factors. As a result, developing self confidence in a lot of ways will be beneficial for developing the social skills.